Peningkatan Kualitas Gerakan Taman Baca “Pustaka Daun” melalui Penerapan Library Automatization - Muhammad Fikri Hidayattullah; Taufiq Abidin; Dega Surono Wibowo; Dyah Apriliani; Yustia Hapsari (Universitas Mathla'ul Anwar Banten, 2021)
IMPROVING THE QUALITY OF GARDEN READ MOVEMENT ”PUSTAKA DAUN” THROUGH THE IMPLEMENTATION OF AUTOMATED LIBRARY. Pustaka Daun is a reading park at the Politeknik Harapan Bersama Tegal which is managed by a group of students. The existence of this library is to enliven and enliven the tradition of traditional literacy. The traditional literacy tradition that discusses sitting together studying and discussing certain themes from a book then discussing it together. Until now Pustaka Daun already has quite a large collection of books. However, library management is still limited and has not been finalized, especially in the collection of collection books. Seeing this phenomenon emerged to help Pustaka Daun managers in managing their library automatically. For this reason, through Community Service activities will provide training to the Leaf Library administrators to manage the library automatically with SLiMS software. The software is a Contents Management System (CMS) web-based tool that can be used easily and is simply installed. Through the implementation of SLiMS, Pustaka Daun management process will be even more organized because everything has been automated by the system. Community Service activities are carried out by providing training using SLiMS, starting from installation to library management. This activities are carried out well thanks to teamwork between lecturers and students. The lecturer presents the material and students participate in assisting and assisting the participants who helped during the training. In addition, the Community Service team provided books to add to the Pustaka Daun collection. After attending the training, the management succeeded in implementing SLiMS in library management.